Coupling Bimetallic NiMn-MOF Nanosheets on NiCo2O4 Nanowire Arrays with Boosted Electrochemical Performance for Hybrid Supercapacitor. (May 2022) - Zhang, Jing; Huang, Jiajie; Wang, Liang; Sun, Peiheng; Wang, Peijia; Yao, Zhujun; Yang, Yefeng
Highlights: The NiCo2 O4 @NiMn-MOF shows high specific capacity upon mn introducing. Flexible solid-state supercapacitor was fabricated using NiCo2 O4 @NiMn-MOF. The device achieves a high energy density of 48.2 Wh/kg at 1606.3 W/kg. The device exhibits both excellent flexibility and electrochemical durability. Abstract: As promising electrode materials for supercapacitors, metal-organic frameworks (MOFs) with rich porosity, large surface area and abundant redox sites have attracted increasing attention. Nevertheless, the intrinsically interior electrical conductivity and ease of agglomeration for most MOFs have largely restricted their energy storage application. In this work, we report the controlled fabrication of bimetallic NiMn-MOF nanosheets on the surface of NiCo2 O4 nanowire arrays to form NiCo2 O4 @NiMn-MOF core-shell structure and investigate the effect of Mn incorporation in Ni-MOF shell on the electrochemical performance of the hybrid arrays in supercapacitors. Benefitting from the delicately designed structures and compositions, the optimal NiCo2 O4 @NiMn-MOF electrode presents an extraordinarily high specific capacity of 243.0 mAh/g at 2 mA/cm 2 . We further assembled a flexible solid-state hybrid supercapacitor with NiCo2 O4 @NiMn-MOF and activated carbon as electrodes, exhibiting a high energy density of 48.2 Wh/kg at 1606.7 W/kg, accompanied by excellent mechanical flexibility and electrochemical durability. This work demonstrates a new approach for developing novel MOF array-based electrode materials with boosted electrochemical performance in the field of flexible energy storage devices. Graphical abstract: Image, graphical abstract